Deceleration capacity: A novel predictor for total mortality in patients with non-ischemic dilated cardiomyopathy. (15th October 2016) - Demming, Thomas; Sandrock, Sarah; Kuhn, Christian; Kotzott, Laura; Tahmaz, Nihat; Bonnemeier, Hendrik
Abstract: Objectives: We hypothesized that deceleration capacity (DC), a novel marker of cardiac autonomic modulation, is an independent predictor for mortality in patients with non-ischemic dilated cardiomyopathy (NICM). Background: NICM is associated with a high risk for sudden cardiac death (SCD). However there are no clinically established parameters available for risk stratification beyond LVEF. DC has been previously shown to be a strong independent predictor for total mortality in patients after myocardial infarction. Methods: Holter-ECG recordings of 201 patients NICM (83.1% male, mean age: 61.4 years, mean LVEF: 33.3%) were analyzed by the method of phase-rectified-signal-averaging (PRSA) to obtain DC. Results: During a minimum follow-up of 40 month 59 patients died. Kaplan Meyer Analysis showed a significantly higher mortality in patients with a DC below 4.5 ms (log rank p = 0.012) irrespective to the presence of atrial fibrillation. Conclusions: Impaired DC is a powerful independent predictor for mortality in patients with NICM.